Notary Role in The Making of Certificate Buy and Sell Binding Agreement For Legal Certainty - Astri Rubbih; Sulistyandari Sulistyandari; Rahadi Wasi Bintoro; Sanyoto Sanyoto (Authentica, 2021)
The role notary in making the sale and purchase agreement deed and the deed of power to sell and sell not appropriate, so there is no legal certainty for the parties who enter into the agreement before the notary. Decision 1603K/PDT/2013, an agreement that was originally payable with a guarantee certificate, but the deed was made a sale and purchase agreement. This type of research is normative or doctrinal legal research. The results of the research and discussion show that the Notary Public does not carry out his role in accordance with the Law on Notary Position, namely not fulfilling the authentic deed making procedure, not reading the deed he has made. Legal consequences for Notaries who do not play the role of a notary according to the Notary Code of Ethics for the Honorary Council may impose sanctions on the Notary. Suggestions from a Notary Public authorized in making Deeds are obliged to implement the provisions of the Law on Notary Position and the code of ethics. The legal consequence for a notary should be that a notary who does not carry out his role has his license revoked.Keywords: Role of Notary, Sale and Purchase Agreement (PPJB), Power to Sell